Does CSR Disclosure Play a Role in Moderating the Effects of Profitability and Free Cash Flow on Firm Value? - Hafizatun Nufus; Muhammad Arfan; Mulia Saputra (Institute of Multidisciplinary Research and Community Service, 2026)
This study aims to examine the role of CSR disclosure in moderating the effects of profitability and free cash flow on firm value among companies in the consumer cyclical sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using purposive sampling, comprising 39 companies and 117 observations over 3 years (2021–2023). This study employs a quantitative approach using secondary data sourced from annual financial statements and sustainability reports. The data were analyzed using a fixed-effects model and moderated regression analysis. The results indicate that profitability has no effect, whereas free cash flow has a negative effect on firm value. Furthermore, CSR disclosure does not moderate the effect of profitability; however, it does moderate the effect of free cash flow by weakening its negative impact on firm value. Thus, it can be concluded that CSR disclosure does not play a role in moderating the effect of profitability on firm value. However, it does play a role in moderating the negative effect of free cash flow on firm value. These findings suggest that investors will hold a negative perception of companies with high levels of free cash flow; however, this negative perception will diminish when the company discloses a high level of CSR. Keywords: Firm value, Profitability, Free cash flow, CSR disclosure, Consumer cyclicals.